Use of Psychotropic Medications in Breastfeeding Women. Issue 12 (17th July 2017) - Kronenfeld, Nirit; Berlin, Maya; Shaniv, Dotan; Berkovitch, Matitiahu
Abstract : Background: Breastfeeding women who are prescribed with psychotropic medications on a regular basis are often concerned, regarding the possible implications of such treatment on the breastfed infant. A mother's well‐being has a direct influence on the well‐being of the baby. However, the notorious reputation of psychotropic medications may lead to suboptimal prescribing by the physician and poor adherence by the mother. Methods: A PubMed search (from 1976 through February 2017) was conducted for commonly used psychotropic drug classes, as well as individual medications commonly prescribed in these classes, along with the MeSH terms "breastfeeding"/"lactation". In each case, we chose studies that describe the pharmacokinetics of passage into breast milk and/or adverse effects in breastfed infants. Results: No large‐scale controlled studies regarding the safety of psychotropic medications in breastfeeding mothers were reported. Based on case reports and small studies, most psychotropic medications produce low milk levels and low plasma levels in the infant, while serious adverse effects in the breastfed infant are rarely reported. Safety data for some psychotropic medications are still unavailable. Conclusion: According to the data available in the literature to date, most psychotropic medications are expected to produce low levels in breast milk with no clinical importance. Nevertheless, an individual risk‐benefit assessment of a proposed treatment should always be performed, as inter‐individual differences may have a substantial effect on the breastfeeding infant's response to the treatment. Further studies and additional objective data are needed to consolidate and improve our current knowledge of psychopharmacotherapy in breastfeeding women. Birth Defects Research 109:957–997, 2017. © 2017 Wiley Periodicals, Inc.